REHABILITATION RECOVERY AFTER ABDOMINOPLASTY - Horopashna, S. A.; Horoshko, V. I. (Rehabilitation and Recreation, 2023)
The relevance of intervention during cesarean section in modern obstetrics has not diminished. Since the frequency of caesarean sections increases many times, the deformation of the anterior abdominal wall after childbirth is a frequent phenomenon that causes dissatisfaction with one’s own body and forms psychological syndromes. In this case, the problem can be solved with abdominal surgery. In addition to the therapeutic and aesthetic effect, abdominoplasty also has important social consequences. According to statistics from the International Aesthetic/Cosmetic Procedures Survey (ISAPS) 2018, it ranks 4th among all plastic surgery procedures in the world. The purpose of the study is to investigate the problem of abdominoplasty, to form a step-by-step rehabilitation plan for patients, and to describe the most complete recovery and ways to prevent complications. The main categories of people who need correction of the deformity of the anterior abdominal wall are obese patients or patients after sudden weight loss or significant weight loss due to childbirth. A satisfactory functional result in the postoperative period is possible only with a complex of means and methods of physiotherapy. Research materials and methods. The following research methods were used in the work: analysis of scientific and methodical literature and information sources on the research topic; instrumental research methods, sociological research methods, functional state assessment methods. The main group of women in labor and the control group after abdominoplasty were formed. Their average age is 30 years. The research was conducted during 2021–2022 on the basis of the “3rd City Clinical Polyclinic of the Poltava City Council”, Poltava, Ukraine. The consent of the management and the studied patients was obtained for participation in the study. Research results. The obtained results indicate that the developed physiotherapeutic complex can improve the process of restoring the physical and functional state of the woman in labor. Many authors report that the use of physical therapy, massage, physical therapy, diet, compression underwear, mechanotherapy, and kinesiotaping showed positive results in the rehabilitation process of women in labor after abdominoplasty. Conclusions. Physical rehabilitation of women in labor after abdominoplasty should include therapeutic exercises, massage, physical therapy, diet, wearing compression underwear, mechanical therapy.